2019
DOI: 10.1002/nafm.10316
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics and Evaluation of Management Scenarios for White Sturgeon in the Sacramento–San Joaquin River Basin

Abstract: Recent surveys suggest a declining population of White Sturgeon Acipenser transmontanus in the Sacramento–San Joaquin River basin (SSJ), California. Probable reasons for the decline include overharvest and habitat degradation compounded by poor recruitment during recent droughts. Despite the importance and status of White Sturgeon, knowledge of their population dynamics in the SSJ remains incomplete and additional information is needed to further inform management decisions. The purpose of this study was to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 77 publications
(271 reference statements)
0
24
0
Order By: Relevance
“…Fish in this age range are below the slot limit, and below-slot fish, in our study, tended to be found lowest in the system, in areas tending toward higher salinity, compared with larger fish. Note that the youngest fish in our dataset was estimated at 7 years old based on the growth curve presented in Blackburn et al (2019), which Sellheim et al (2022) indicate would tend to be using higher-salinity habitats. The discrepancy in ages between these studies also highlights that telemetry data on juvenile white sturgeon are limited, resulting in uncertainty over their habitat use and movements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Fish in this age range are below the slot limit, and below-slot fish, in our study, tended to be found lowest in the system, in areas tending toward higher salinity, compared with larger fish. Note that the youngest fish in our dataset was estimated at 7 years old based on the growth curve presented in Blackburn et al (2019), which Sellheim et al (2022) indicate would tend to be using higher-salinity habitats. The discrepancy in ages between these studies also highlights that telemetry data on juvenile white sturgeon are limited, resulting in uncertainty over their habitat use and movements.…”
Section: Discussionmentioning
confidence: 99%
“…For the PERMANOVA analyses, we considered three classes of fish size relative to the current slot limit on the white sturgeon recreational fishery in California, which permits only fish between 40 in (102 cm) and 60 in (152 cm) fork length to be kept. Blackburn et al (2019), analyzing fish from the same region, showed that typical white sturgeon are in the fishery from ages 10 to 15. Using growth curves from Blackburn et al (2019), we extrapolated length-at-tagging forward in time and classified fish as below slot, in the fishery, or above the slot limit at each water year.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The estuary population was nearly extirpated in the late 19th century from commercial harvest, but now supports a recreational fishery (Chadwick 1959;Skinner 1962;Parks 1978;Kohlhorst 1980). However, current harvest levels are unsustainable and, together with the loss of habitat, represent a serious threat to the continued existence of the population (Blackburn et al 2019).…”
Section: Research Estuarine Habitat Use By White Sturgeon (Acipenser mentioning
confidence: 99%